Development of Local Wisdom-Based Inquiry E-Module on Anaerobic Respiration to Improve Students' Science Process and Collaboration Skills in Phase F, State Senior High School 2 Plus Panyabungan - Rahmadani Purba; Muhyiatul Fadilah; Helendra; Fitri Arsih (Postgraduate, University of Mataram, 2025)
This study was designed to create an inquiry-based e-module that integrates local wisdom for learning the topic of Anaerobic Respiration. The aim was to ensure that this e-module is valid, practical, and effective in improving students' scientific process skills (SPS) and their ability to collaborate, especially for students in Phase F at SMA Negeri 2 Plus Panyabungan. The background of this study is based on the low level of scientific process skills, especially in connecting concepts (11%) and analyzing (24%), as well as weak collaboration skills (53.33% included in the low category). This study followed the research and development (R&D) method using the Plomp model, which consists of three phases: initial investigation, prototype development, and evaluation. The results showed that the developed e-module was highly valid, with an average score of 95.37%, very practical as indicated by student responses (93.01%) and teacher responses (97.92%), and effective in improving scientific process skills, evidenced by significant results (Sig. 0.000 < 0.05), and in improving student collaboration, which increased from the sufficient category to the very high category. Therefore, it can be concluded that this inquiry-based e-module that integrates local wisdom is suitable for use as an innovative learning resource to improve scientific process skills and collaboration among students studying Anaerobic Respiration.